Integrating Constructivist and Inquiry Based Learning in Chemistry Education: A Systematic Review - Suryati, Suryati; Adnyana, Putu Budi; Ariawan, I PutuWisna; Wesnawa, I Gede Astra (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This study systematically examines the integration of constructivist and inquirybased learning (IBL) strategies in chemistry education, emphasizing their transformative potential for enhancing student engagement, conceptual understanding, critical thinking, and problem solving skills. Utilizing a systematic review methodology, 30 peer reviewed articles from credible databases such as Scopus and Web of Science were analyzed. The findings reveal that gamification, virtual reality (VR), molecular visualization, and guided inquiry significantly improve learning outcomes by contextualizing abstract concepts and fostering active participation. Gamification and VR were particularly effective at the high school and tertiary education levels, respectively, while inquiry based laboratory activities enhanced higher-order thinking skills. The analysis highlights the theoretical alignment of these strategies with constructivist principles and their practical application in modern pedagogy. Despite their benefits, challenges such as resource limitations and insufficient teacher training persist, hindering wider adoption. Addressing these barriers through professional development, resource investment, and innovative curriculum design is essential for maximizing the impact of constructivist and IBL approaches. This study provides actionable recommendations for educators, policymakers, and researchers, advocating for systemic changes to advance chemistry education in diverse learning contexts. By combining theoretical insights with practical applications, this research underscores the importance of active, inquiry driven learning environments for preparing students to excel in STEM fields.